DECAPOD CRUSTACEANS NEW TO ANDAMAN AND NICOBAR ISLANDS - Thomas, M M (Indian Journal of Fisheries, 2011)
During the studaes on the taxonomy of In&run deoapods, 13 species we’re collected ilrom Andaman a.nd Nicohalf ’blands. Of thelse, 6 petnooids viz., Penaeus canaJiculatus, P. merguiensis, Metapenaeus dobsoni, M. affinis, M. burkenroadi aoo Parapenaeopsis cornuta; 2 speoies Qf pagu6d crabs viz., Calcinus latens and Pagurus jeh1itor ’and 1 co’enohiitid viz., Coenobita clypeata were lI’epolfitied f,rom ,these is1runds for the first time. Points of taxonomic intelfe’st ’a,re’ alIsO’ discussed.